Town planning in the late Middle Ages. About building plots, streets and Standard dimensions in Elburg and some other towns (Bulletin KNOB, 2003)
This article deals with the layout of the new town of Elburg around 1400, the layout of some other new towns and town extensions in the Netherlands during the fourteenth century, and with the wider, international context of this town planning. For instance, there is evidence that from the twelfth to the fifteenth century a rational type of town planning and urban design were practised, both in the layout of new towns and in town extensions.In so far as the situation allowed it, general organising principles were adopted in the planning and building of towns. Standard dimensions were used for building plots, building blocks, the width of streets and canals, and often these were in rational proportion to each other. The dimensions and regularity could vary depending on the (geographical, economic, social, legal, structural etc.) conditions locally. It is utter nonsense to describe the development of medieval towns as organically grown, without direction, as is only too often done.